Experimental Research on Frost Heave Characteristics of Gravel Soil and Multifactor Regression Prediction - Xiaoyong Long; Guoping Cen; Liangcai Cai; Yue Chen (Advances in Materials Science and Engineering)
Gravel soil is usually considered to be insensitive to frost heave. However, many frost heave deformations of foundation in seasonal frozen region indicate that gravel soil may also produce frost heave under certain special conditions. In order to gain a deep insight into the frost heave characteristics of gravel soil, a series of laboratory experiments on one-dimensional frost heave were conducted under the open- and closed-water replenishing condition using an improved experiment apparatus. The influence of various factors including initial moisture content, clay content, compactness, overlying load, and water replenishing on frost-heaving ratio of gravel soil were analyzed. And the basic frost heave characteristics including frost heave amount, frost heave speed, frozen depth, freezing speed, and moisture content distribution after freezing in a gravel soil sample were analyzed. The corresponding mechanisms were also discussed. Results showed that in the open water replenishing condition, there exists a linear relationship between initial moisture content, overlying load, and frost-heaving ratio and a quadratic polynomial relationship between clay content, compactness, and frost-heaving ratio. Frost-heaving ratio in the open water replenishing condition can be found to increase over three times than that under the closed water replenishing condition. Multifactor regression empirical formula was obtained by multiple regression analysis to predict the frost-heaving ratio of gravel soil under certain collocation of factors and levels under the closed water replenishing condition. The significant effects on frost-heaving ratio were, in order, water replenishing > initial moisture content > clay content > compactness > overlying load.